2007
DOI: 10.1590/s0036-36342007000100005
|View full text |Cite
|
Sign up to set email alerts
|

Infant morbidity caused by respiratory diseases and its relation with the air pollution in Juarez City, Chihuahua, Mexico

Abstract: The wide range of risk is quite important and might represent a substantial cost for the health system as well as for the society. Our results emphasize the need to implement preventive and control measures for air pollution and avoid the worsening of the present situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
8
0
3
Order By: Relevance
“…Gouveia and Fletcher (2000) identified a 1% higher risk of infant pneumonia (RR 1.009[1.001, 1.017]) and a similar risk among the under-five age group as a whole (RR 1.005 [0.998, 1.012]). Hernandez-Cadena et al (2007) also reported an increased risk of similar magnitude in Mexican children and infants below age 6 associated with PM 10 exposure (RR 1.007 [0.987, 1.027]).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Gouveia and Fletcher (2000) identified a 1% higher risk of infant pneumonia (RR 1.009[1.001, 1.017]) and a similar risk among the under-five age group as a whole (RR 1.005 [0.998, 1.012]). Hernandez-Cadena et al (2007) also reported an increased risk of similar magnitude in Mexican children and infants below age 6 associated with PM 10 exposure (RR 1.007 [0.987, 1.027]).…”
Section: Resultsmentioning
confidence: 81%
“…Three of the studies were conducted in Brazil (Braga et al 2001; Conceicao et al 2001; Gouveia and Fletcher 2000; Saldiva et al 1994), and the other two studies were carried out in Mexico (Hernandez-Cadena et al 2007) and Chile (Ostro et al 1999). Six of these time series studies identified a relationship between ALRI morbidity or mortality and increases in PM 10 exposure, with relative risk estimates ranging from 1.00 and 1.09 for every 10-μg/m 3 increase in PM 10 exposure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This pollutant also presented a greater statistical significance in the research conducted by Nascimento et al, also in children in Sao Jose dos Campos, in relation to hospitalization for pneumonia 10 . On the other hand, in a study conducted in Mexico, there was no significant relationship between ambient levels of PM 10 and emergency visits for respiratory causes 21 .…”
Section: Discussionmentioning
confidence: 80%
“…There are several epidemiological studies realized at a number of cities in Mexico's northern border, where the relationship between changes in human health and the concentration of air pollutants was analyzed, which only few considered; aerobiological pollutants and the increased incidence of childhood asthma in the specified form were found [16,17]. It may be said that there are virtually no studies that specifically analyzed the air pollutants such as fungal spores and the incidence of childhood asthma, despite the high concentrations of air pollutants of this type, reported in taxonomic studies carried out in different parts of Mexico, [18][19][20].…”
Section: Discussionmentioning
confidence: 99%